2005
DOI: 10.1002/cphc.200500185
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis of Confined Water: Hydrogen Production at a High Dose Rate

Abstract: The production of molecular hydrogen in the radiolysis of dried or hydrated nanoporous controlled-pore glasses (CPG) has been carefully studied using 10 MeV electron irradiation at high dose rate. In all cases, the H2 yield increases when the pore size decreases. Moreover, the yields measured in dried materials are two orders of magnitude smaller than those obtained in hydrated glasses. This proves that the part of the H2 coming from the surface of the material is negligible in the hydrated case. Thus, the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 93 publications
4
38
0
Order By: Relevance
“…The most significant decrease in crystallinity was obtained in nanocomposite gels containing 20 wt% of nanosilica which on irradiation to 100 kGy is almost completely amorphous. The mechanism of nanosilica contribution to the formation of hydroxyl radicals is most likely similar to that proposed by Le Caër et al . They showed that on irradiation in silica/water system, an exciton was formed that may be scavenged by water molecules and further react to produce additional hydroxyl radicals, protons, and hydrogen .…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The most significant decrease in crystallinity was obtained in nanocomposite gels containing 20 wt% of nanosilica which on irradiation to 100 kGy is almost completely amorphous. The mechanism of nanosilica contribution to the formation of hydroxyl radicals is most likely similar to that proposed by Le Caër et al . They showed that on irradiation in silica/water system, an exciton was formed that may be scavenged by water molecules and further react to produce additional hydroxyl radicals, protons, and hydrogen .…”
Section: Resultssupporting
confidence: 67%
“…The mechanism of nanosilica contribution to the formation of hydroxyl radicals is most likely similar to that proposed by Le Caër et al . They showed that on irradiation in silica/water system, an exciton was formed that may be scavenged by water molecules and further react to produce additional hydroxyl radicals, protons, and hydrogen . The increased concentration of reactive species may be the cause of some of the degradation effects observed in nanocomposite gels, such as worsened mechanical properties compared with pure PEO gels irradiated to the same dose.…”
Section: Resultssupporting
confidence: 65%
“…Also, with heavier alkali ions, an increased specific surface between the solid matrix and the porous media induced a larger energy transfer to the water and a larger hydrogen production. This observation is similar to transfers observed many in other materials developing an interface with water . A hydrogen production excess can either be induced by the increase in energy absorption coefficient, or by differences in the energy transfer, for example different trapping of electrons by cations clusters.…”
Section: Introductionsupporting
confidence: 87%
“…However both the confinement and interface effects influence the chemical reactions and these two effects are difficult to isolate from each other in the experiments. Even simple nanoporous materials have complex interfaces 1 that strongly interact with the confined liquids (reactants and products) [3][4][5]. The interface effect can thus hide the hypothetical generic confinement effect or finite size effect.…”
Section: Introductionmentioning
confidence: 99%